Kompetencje rodzicielskie w kontekście odbywania kary pozbawienia wolności - Szczygieł, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The presented article adopts the understanding of parental competence as a kind of skill to be developed and improved, rather than a relatively constant human capacity. This approach opens up space for designing parental programmes for prisoners. It is assumed that their competences are subject to change. During imprisonment, these tend to weaken, but it is possible to boost them through well-designed measures. It should be noted here that any pedagogical activity should be based on a diagnosis of the situation. Therefore, the article consists of ﬁ ve parts: a theoretical introduction presenting the basic terminology of parental competence and the situation of an imprisoned parent in the context of stigmatisation; a short methodological analysis; an in-depth description of the research sample; a synthetic perspective on the results of tests obtained using the Parental Competence Test prepared by A. Matczak and J. Jaworska, followed by a summary.
Keywords: zakład karny; kompetencje rodzicielskie; więzi rodzinne; stygmatyzacja